(3Gdedd hGdOhd aj GdCMcGe heG JOd Ydjg GdCTNGU GdYdhjI hJCKjQGJgG aj GdGLSGe GdSadjIs - (3LYaQ Hf eMeO Hf YeQ GdHdNj, CHh eYTQ , nCoHh nerYnTQ Gdnandcj,J (B272 (3g` s ((3MGLi Ydi GdQGRi s)
(3BNQgG (B:s
(3hGdTeS i Sfjf hGdRgQI M Sfjf hYWGQO cM SfI GdbeQ W Sfjf GfJgi cdGe CHj eYTQ hgh BNQ cdGeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3fSNI KGfjI JJab ai ChdgG eY Chd GdfSNI GdJi HQbe (B423 (3HGNJdGa ai HYV GdCdaGXs
(3cJHJ fbdG Yf fSNI hLeYgG EHQGgje GdMGSH GdeGdci GdefUhQi GdfGUQi HeOjfI GdbGgQI SfI (B759 (3g`s
(3HgG HYV GdCTcGd hGdLOGhds
(3HgG fXGe GdJYbjHIs
(3HChd GdeLehYI Jedc SfI (B1249s
(3bQf GdfSN (B:s
Keywords: (3Gdadcs